Digital-Based Synergy of Campus Communities and Students in Efforts to Prevent Sexual Harassment in The Higher Educational Environment - Munisa; Nofianti, Rita; Putri, Utami Nurhafsari; Audy, Rini Trinasya (JETLi: Journal of English Teaching and Linguistics, 2024)
Sexual violence is defined as any act that, as a result of power dynamics or gender relations, degrades, harasses, or attacks a person's body, causing or possibly causing psychological or physical suffering, as well as interfering with and preventing them from safely and effectively pursuing higher education. Anywhere can experience sexual violence, including on campus. When technology is misused, as in the instance of sexual harassment, a person's ignorance of its use might have detrimental effects. This study combined a qualitative approach with a library research methodology, whereby data was collected from books, journals, and other reading materials, and conclusions and suggestions were drawn in response to the issues found. When it comes to sexual harassment on campus, the researchers found that some incidents happened in locations that students don't often visit—namely, the library room—because there are so many online resources available for information. As a result, the researchers reached conclusions and recommendations regarding how to stop sexual harassment in higher education. They suggested creating online action in the form of slogans and posters that are shared by colleges, students, and the campus community through social media platforms already in place, as well as providing a platform or facility like a Counseling Service Unit related to sexual violence as a form of complaint to the Integrated Service Unit.